2006
DOI: 10.1016/j.athoracsur.2006.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results in T2N0M0 Nonsmall Cell Lung Cancer Patients With Large Tumors 5 cm or Greater in Diameter: What Regulates Outcome?

Abstract: Background:We assessed the surgical results along with the clinical and biological features of non-small cell lung cancer (NSCLC) patients with localized large tumors. Methods:The study population consisted of 86 NSCLC patients who underwent complete resection of tumors 5 cm or larger in diameter in stage IB (T2N0M0). We immunohistochemically assessed the expression of angiostatin and endostatin. Results:The median tumor size was 6.0 cm (range, 5-14 cm). The operative procedures used were lobectomy in 71 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
1
1
1
1
Order By: Relevance
“…Pleural invasion status is well recognized as a strong prognostic factor. 9,10,15,22,24,25 Our study also confirmed pleural invasion as an independent predictor. Although the stage IB group could not be classified into groups with obviously different prognosis by IVI only, we found a worse prognosis in patients with stage IB with both IVI and pleural invasion than in patients without these factors.…”
Section: Discussionsupporting
confidence: 80%
“…Pleural invasion status is well recognized as a strong prognostic factor. 9,10,15,22,24,25 Our study also confirmed pleural invasion as an independent predictor. Although the stage IB group could not be classified into groups with obviously different prognosis by IVI only, we found a worse prognosis in patients with stage IB with both IVI and pleural invasion than in patients without these factors.…”
Section: Discussionsupporting
confidence: 80%
“…Visceral pleural invasion has been recognized to be another strong prognostic factor associated with increased risk of recurrence and death;5,13,23,2730 however, some researchers have found otherwise,4 and our study did not find any correlation with tumor recurrence.…”
Section: Discussioncontrasting
confidence: 82%
“…In the current study, we divided the tumors into P0, P1, and P2 subgroups according to the depth of VPI. Using a similar classification, Ohta and colleagues 19 reported patients with P2 showed a significantly poorer survival and shorter disease-free interval than did patients with P0 and P1. Our patient cohort demonstrated an actual 5-year survival of 64.3% in the P0 group.…”
Section: Discussionmentioning
confidence: 99%